The Matthean characterisation of Jesus by God the Father - Viljoen, Francois P. (HTS teologiese studies, 2019)
This article uses a narrative analysis to contribute to the discourse on the characterisation of Jesus in the Matthean Gospel. Characterisation can be achieved in various ways. Much is revealed about characters through their actions and words, and how other role-players in the text respond to them. Sometimes there is a narrator who tells the reader about a character. The kind of character depends on the traits or personal qualities of that character and how that character performs during specific incidents. Along with God himself, Jesus forms the principal character in the First Gospel. His teachings and actions are central to the text and the actions of other characters are directed towards him. The article focuses on one aspect of characterisation, namely, on what characters say about Jesus. Such words can come from supporters or antagonists. The article concentrates on what God the Father says in support of Jesus. The Father’s point of view is normative in this narrative. The evangelist utilises the utterances of God the Father as a narrative strategy to gradually assure the prominence and authority of the character of Jesus. Matthew’s narrative clearly recounts Jesus’ authority – an authority that comes from God and not only points towards him but also finally becomes his own. The Father attests that Jesus is greater and more authoritative than any previous messenger of God. It is Jesus who ultimately states that all authority has been bestowed upon him and therefore he can send out the disciples with his Great Commission. God’s heavenly voice expresses the significant status of Jesus as the main character and exposes the malignity of his antagonists.